2014
DOI: 10.1111/pan.12360
|View full text |Cite
|
Sign up to set email alerts
|

Pressure recording analytical method and bioreactance for stroke volume index monitoring during pediatric cardiac surgery

Abstract: Pressure recording analytical method and bioreactance provided similar SVI estimation at stable hemodynamic conditions, while bioreactance SVI values appeared significantly lower than PRAM at the end of CPB and after fluid replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In a recent study, Garisto et al . evaluated the difference between stroke volume index (SVI) measured by PRAM and bioreactance and their ability to track changes after treatment of children undergoing cardiac surgery. They observed that under stable hemodynamic conditions, both methods provided similar SVI estimations, although bioreactance SVI values appeared significantly lower than PRAM after fluid replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Garisto et al . evaluated the difference between stroke volume index (SVI) measured by PRAM and bioreactance and their ability to track changes after treatment of children undergoing cardiac surgery. They observed that under stable hemodynamic conditions, both methods provided similar SVI estimations, although bioreactance SVI values appeared significantly lower than PRAM after fluid replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Bojan and coauthors also hypothesized that cardiopulmonary bypass would have a significantly greater role than low cardiac output on AKI development. It must be acknowledged that no direct measure of cardiac output was included in their study and its assessment is currently poorly applied in the context of pediatric cardiac surgery [11] and pediatric intensive care [12, 13]: it would be interesting to perform a similar analysis including direct cardiac output estimation.…”
Section: Main Textmentioning
confidence: 99%
“…PIM2 score is utilized in our hospital to assess critical illness severity of children admitted to our pediatric intensive care units (PICUs) (13). Finally, after CPB, CI is routinely monitored at our institution by pressure recording analytical method (PRAM) (14): it is a minimally invasive hemodynamic monitoring system based on mathematical analysis of the invasive arterial waveform recorded at a high sampling rate (1000 Hz). The area under the pressure wave is examined during the whole cardiac cycle, including the postdicrotic notch phase, and it is utilized to assess the patients' stroke index.…”
Section: Evaluated Scores and Hemodynamic Measurementsmentioning
confidence: 99%
“…Median Aristotle score was 8 (6)(7)(8)(9)(10) and VIS, at CPB weaning, was 16 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In all cases, it was possible to retrieve hemodynamic PRAM data recorded throughout the procedure.…”
Section: Description Of Enrolled Patientsmentioning
confidence: 99%